Development of stereo matching algorithm based on sum of absolute RGB color differences and gradient Matching - Rostam Affendi Hamzah; M. G. Yeou Wei; N. Syahrim Nik Anwar (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper proposes a new stereo matching algorithm which uses local-based method. The Sum of Absolute Differences (SAD) algorithm produces accurate result on the disparity map for the textured regions. However, this algorithm is sensitive to low texture areas and high noise on images with high different brightness and contrast. To get over these problems, the proposed algorithm utilizes SAD algorithm with RGB color channels differences and combination of gradient matching to improve the accuracy on the images with high brightness and contrast. Additionally, an edge-preserving filter is used at the second stage which is known as Bilateral Filter (BF). The BF filter is capable to work with the low texture areas and to reduce the noise and sharpen the images. Additionally, BF is strong  against the  distortions due to high brightness and contrast. The proposed work in this paper produces accurate results and performs much better compared with some established algorithms. This comparison is based on the standard quantitative measurements using the stereo benchmarking evaluation from the Middlebury.